Repair, maintenance and associated services related to roads and other equipment (MENA Report, 2015)
Implementing agency : ANAS Compartimento della Viabilit? per la Puglia Viale Luigi Einaudi 15 For the attention of: Dirigente Amministrativo 70125 Bari ITALY Telephone: +39 0805091320 Fax: +39 0805091488 E-mail: c.rosito@stradeanas.it Internet address(es): General address of the contracting authority:...